Hubungan Perhatian Orang Tua dan Kompetensi Kepribadian Guru dengan Kemandirian Belajar Siswa Kelas IV SDN 54 Banda Aceh: Penelitian - Farah Fadilla; Rahmattullah; Kembang Ayu Agustya (PT PUSTAKA CENDEKIA GROUP, 2026)
Learning independence is a crucial competency for elementary school students, supporting both successful learning outcomes and character development. Parental attention and teachers' personality competence are viewed as factors that potentially influence the development of students' learning independence. This study aimed to analyze the relationship between parental attention, teachers' personality competence, and the learning independence of fourth-grade students at SDN 54 Banda Aceh. A quantitative approach using a correlational survey design was employed. The study sample consisted of 26 students selected via purposive sampling. Data were collected using Likert-scale questionnaires and analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Pearson Product Moment correlation test with the aid of IBM SPSS Statistics software. The results revealed a positive and significant relationship between parental attention and students' learning independence, with a correlation coefficient of 0.447 and a significance level of 0.022 (p < 0.05). Conversely, teachers' personality competence showed no significant relationship with students' learning independence, indicated by a correlation coefficient of 0.292 and a significance level of 0.148 (p > 0.05). The study concludes that parental attention is a more dominant factor than teachers' personality competence in fostering students' learning independence. These findings are expected to provide valuable insights for schools and parents to strengthen their collaboration in sustainably enhancing students' learning independence.